METODE RESOLUSI KONFLIK OLEH LEMBAGA ADAT MELAYU (LAM) RIAU DALAM MENYELESAIKAN SENGKETA TANAH ULAYAT DI KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Roy Muhammad Akbar; Isnaini Muallidin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
Often occurs Conflict of Ulayat Land in Rangsang District with PT.SRL occurred because of PT.SRL intentionally seized Ulayat land of Buana Rangsang. Therefore the task of the Malay Customary Institution (LAM) of Riau is to defend and safeguard the rights of indigenous and tribal peoples so that no more customary land conflicts occur.This research uses a descriptive qualitative method, data sources can be obtained through observation, literature study, documentation and interviews with several key informants who know very well about the conflicts that have occurred.The results of this study explain that the Malay Customary Institution (LAM) of Riau has conducted conflict resolution by integrating, second is a compromising method. Because the company not wanting to make peace, the Customary Institution (LAM) of Riau in this case the was stimulated to make efforts to resolve the dominating.